Models of intellectual property governance and administration - Thumm, Nikolaus, 1967-; Blind, Knut, 1965-; Stolz, Christopher (World Intellectual Property Organization, 2024)
"Models of Intellectual Property Governance and Administration documents and analyzes prevailing approaches, trends and emerging directions in IP governance and administration. This study will equip policymakers with valuable insights to support well-informed decisions in designing IP governance and administration frameworks, thereby unleashing the full potential of the intellectual property system for the benefit of society."--